Respons Pertumbuhan, Fisiologi, dan Produksi Kedelai terhadap Pemberian Pupuk Nitrogen dengan Dosis dan Waktu yang Berbeda - Firdaus Puja Santana; Munif Ghulamahdi; Iskandar Lubis (Jurnal Ilmu Pertanian Indonesia, 2021)
Fertilization is needed to support the growth of soybean plants. Nitrogen is a type of fertilizer that is needed by soybeans in considerable amounts. Aplication of nitrogen at different times is able to affect the production and quality of soybean seeds. The purpose of this study was to attain information about the morphology, physiology, and production responses of two soybean varieties to the supply of N. This research was conducted at the Cikabayan Experimental Station, IPB University, Dramaga, Bogor Regency. This study used a completely randomized block design with two factors, namely two soybean varieties consisting of Tanggamus and Biosoy 1, and four combinations of N fertilizer doses that were without N fertilization, fertilized N at planting date, fertilized N at the seed filling phase, and fertilized N at planting date+seed filling phase with two replications. The dosage of urea fertilizer used was 25 kg ha-1, so that the N dosages is obtained 11,5 kg ha-1. The results showed that the application of N fertilizers at planting and during the seed filling phase (N3) was an effective time to increase soybean production. Keywords: fertilization, morphology, seed quality